2020
DOI: 10.1111/jace.17553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying conditions on the stress and weight development of capillary suspensions

Abstract: Cracking of suspensions during drying is a common problem. While additives, for example, binders and surfactants, can mitigate this problem, some applications, such as printing conductive pastes or sintering green bodies, do not lend themselves to the use of additives. Capillary suspensions provide an alternative formulation without additives. In this work, we use simultaneous stress and weight measurements to investigate the influence of formulation and drying conditions. Capillary suspensions dry more homoge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…Such a behavior had been previously investigated with capillary dispersions (ternary mixtures of solid particles immiscible fluids), where stress build-up comes from frustrated shrinkage while stress relief is derived from relaxation due to the action of strong particle networks. Under specific formulations and drying conditions, the latter can dominate to the extent that cracking may be prevented [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such a behavior had been previously investigated with capillary dispersions (ternary mixtures of solid particles immiscible fluids), where stress build-up comes from frustrated shrinkage while stress relief is derived from relaxation due to the action of strong particle networks. Under specific formulations and drying conditions, the latter can dominate to the extent that cracking may be prevented [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The These results are consistent with findings previously reported by Fischer and Koos. 38 They conducted drying experiments of capillary suspensions using mass spectrometry (MS) with thermogravimetric analysis (TGA) and found that the secondary fluid evaporated rapidly after the constant rate period. The drying process can be divided into the constant rate period and the falling rate period.…”
Section: Resultsmentioning
confidence: 99%
“…32 They reported that the secondary fluid evaporates later than the bulk fluid, thereby maintaining the particle network structure, increasing the distribution uniformity of the particles, and inhibiting cracks as the local stress distribution becomes uniform. Fischer and Koos 38 investigated the drying mechanism of capillary suspensions with various drying conditions and compared with a pure suspension. They reported that the change in the drying pattern could suppress film defects such as trenches and pinholes.…”
Section: Introductionmentioning
confidence: 99%
“…While this can be advantageous for the formation of porous supraparticles [76] or in the threedimensional printing of structured porous materials [45,[77][78][79], the changes due to evaporation should be better understood. The bridges do seem to persist for long times, even if they have a higher vapor pressure than the bulk liquid [80], leading to a reduction in cracking [81][82][83][84], but the link between the drying conditions and formulation should be better understood. Furthermore, the influence of the bridges on particle motion and segregation of small particles, for example, binder, should be explored.…”
Section: Discussionmentioning
confidence: 99%